John Smith correspondence - Smith, John, 1750-1836.
ALS from Smith to William Davidson of Winchester, Va., relating to national politics and life in Washington, D.C.
U.S. representative from Virginia, public official, and army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Davidson, William, -- active 1808 -- Correspondence; United States -- Politics and government -- 1801-1809.; Virginia -- Politics and government -- 1775-1865.; Washington (D.C.) -- Social life and customs; Winchester (Va.) -- History; Army officers; Public officials -- Virginia; Representatives, U.S. Congress -- Virginia